Konjunktives Erfahrungswissen Lehramtsstudierender zu Inklusion - Viermann, Mia (Perspektiven sonderpädagogischer Forschung, 2022)
The realization of inclusion in schools makes a significant contribution to the development towards an inclusive society (cf. Lütje-Klose et al. 2018a, p. 9), as social practices are not only reproduced in schools, but also newly produced. These practices are carried on in extra- and postschool fields of action (cf. Sturm 2018b, p. 251; Powell 2016, p. 681; Budde 2012, p. 530ff.). Although the introduction of inclusion confronts the entire multi-level system of schools with the task of critically questioning existing structures, concepts, and practices and working on them in an inclusion-oriented manner (cf. Lindmeier & Lütje-Klose 2019, p. 590), the requirements in the field of action of teachers are becoming more complex. Teachers are not only responsible on the meso and micro level of the school system, but also interactively involved in the (re)production of social practices in the school practice (cf. Sturm 2018, p. 254ff.). It is up to teacher education to prepare student teachers to accept the challenge of school inclusion and to adapt traditional educational structures and contents in an inclusion-oriented way. The dissertation aims at reconstructing the knowledge that students of different teacher training programs have about inclusion-related subjunctive experiences during their studies. For this purpose, group discussions with students of special education and secondary school teaching are analyzed using the documentary method. The reconstructions provide information about how the participating student teachers anticipate and cope with inclusion as a challenge of school practice. Based on the findings, implications for the (re)orientation of educational structures and contents of teacher education are finally presented for discussion.